Zróżnicowanie przestrzenne dochodów własnych budżetów gmin w Polsce w latach 2007–2015​ - Jarosiński, Krzysztof (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2018)
The experience of systemic transformation in Poland and the progressing socio-economic development prove that the importance of organizational units classified conventionally as a part of the public sector has increased significantly. It turned out that during rapid economic and social changes, the development of technical and social infrastructure became one of the drivers of development. In the conditions of the market economy in Poland, two important areas related to the functioning of the public sector have come to the fore: quantification of objectives and tasks necessary for the proper functioning of the state and society and ensuring efficient sources of financing these tasks. In this paper the aim of the research was to analyse and assess the financial situation of municipal territorial self-government units in Poland in 2007–2015. The research results clearly indicate the existence of differences in the level of budget revenues between differentiated territorial self-government units in the years 2007–2015. In that time the budget revenues of communes increased and significant positive changes in the budgetary situation of municipal local government units took place, in almost all regions these incomes doubled. This increase was accompanied by persistence of disproportions between less developed regions and regions that were economically and socially developing faster. In the discussed period, we had to deal with the improvement of the income situation of the budgets of local government units, with the simultaneous increase in the differences in the level of income with all the consequences associated with this for future development.